PENGARUH 2,4- D TERHADAP PENINGKATAN KUALITAS DAN KUANTITAS KALUS YANG DIINDUKSI DENGAN KOMBINASI AUKSIN DAN SITOKININ PADA KULTUR DAUN RUMPUT BENGGALA ( Panicum maximum) VARIETAS TRICHOGLUME - Marna Eoh (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2021)
To determine the effect various concentration 2, 4, 6 and 8 mg/l of 2,4- D (2,4- dicloropenoxy acetic acid) on callus induction of Benggala grass variety Trichoglume leaf culture on Murashige and Skoog (MS) standard medium and its organogenesis stimulated using deffent concentration of growth regulator, namely [N6- (2- isopenteny)- adenine] or 2iP (0, 0.2 and 1.0 mg/l ) and (l- naphthalene acetic ent, wacid) or NAA (0, 0.03, 0.16 and 3.0 mg/l) were performed. Percentage of callus were measured and organogenesis from callus were subjected to description analysis . The results showed that callus induction was optimum when 2,4-D was treated at 4 mg/l, friable callus were produced. Percentage production of callus week 4 was 46.2 percent, while using 8 mg/l 2,4 –D the callus production was about 59.7 percent yellowish coloured and more compact callus were produced. Combination of 0 mg/l 2iP ( auxin) + 3mg/l (cytokinin) at 3 weeks showed reseilted 100 % of calluses produced roots, the highest amaunt roots (9,0) was observed in combination 0 mg/l 2iP + 3 mg/l NAA, and the longest root (17,0 mm) was recorded in combination 0 mg/l 2iP + 3 mg/l NAA. Calluses yielded varied from white, yellowish to brown colour.